Relationships of neurosensory disorders and reduced work ability to alternative frequency weightings of hand-transmitted vibration - Massimo Bovenzi; Andrea Prodi; Marcella Mauro (Nordic Association of Occupational Safety and Health (NOROSH), 2015)
OBJECTIVE: This cohort study aims to compare the performance of alternative frequency weightings of hand-transmitted vibration (HTV) for the assessment of the exposure-response relationships for neurosensory disorders and reduced work ability among HTV-exposed workers. METHODS: In a 3-year follow up study, the occurrence of neurosensory symptoms and reduced work ability, and the response to quantitative sensory testing (grip force, manipulative dexterity, touch sensation) were investigated in 249 HTV-exposed workers and 138 healthy controls. Among the HTV-exposed workers, the sensory outcomes were related to measures of daily vibration exposure expressed in terms of 8-hour energy-equivalent frequency-weighted acceleration magnitude [A(8)]. To calculate A(8), the acceleration magnitudes of vibration were weighted by means of four alternative frequency weightings of HTV. RESULTS: The occurrence of neurosensory symptoms, reduced work ability, and abnormalities of sensory tests was greater among the HTV-exposed workers than the controls. Among the HTV-exposed workers, the deterioration of neurosensory outcomes and the reduction of work ability increased on par with the measures of vibration exposure. Exposure-response models revealed that the four alternative frequency weightings of HTV provided the same predictions for the probability of finger numbness among the exposed workers (observed 36% versus predicted 32%). CONCLUSIONS: The findings of this study revealed significant dose-response relationships between measures of vibration exposure, sensory disorders, and reduced work ability among the HTV-exposed workers. There were no differences in the prediction of finger numbness between measures of vibration exposure calculated with alternative frequency weightings of HTV.